Macro foundations for macroprudential policy: A survey and assessment - James A. Haley (Centre for International Governance Innovation (CIGI), 2020)
Since the global financial crisis, which disrupted the lives of millions and cast a cloud of uncertainty over the future of millions more, there is greater appreciation of the interconnectedness of large, complex financial institutions, both within a particular jurisdiction and across countries, as well as recognition of the feedback effects and spillovers between the financial system and the real economy. The need today is to mitigate risks in the financial system as a whole, rather than apply a microprudential focus on individual institutions; the challenge is to address the fact that risks in the financial system are greater than the sum of the risks in its parts. Macroprudential policies address this challenge. These policies encompass a host of measures designed to curb excessive risk taking and promote the accumulation of buffers to enhance the resiliency of the financial system. Complementing previous studies on assaying and assessing the full suite of these measures, this paper examines the macroeconomic foundations of macroprudential measures and the connection between them and other policies. Its goal is to explain how macroprudential measures can support other policy instruments, monetary policy in particular, in promoting financial stability and long-term growth, along the way discussing the impact of financial factors on the real economy and how the financial sector interacts with these other instruments.
Keywords: 330; Financial Market Supervision; Financial Crisis; Monetary Policy; Finanzmarktaufsicht; Finanzkrise; Geldpolitik